2017
DOI: 10.1097/md.0000000000006524
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of intra-articular lumbar facet joint pulsed radiofrequency and intra-articular lumbar facet joint corticosteroid injection for management of lumbar facet joint pain

Abstract: Background:This study aimed to demonstrate the effect of intra-articular (IA) lumbar facet joint (LFJ) pulsed radiofrequency (PRF) for the management of LFJ pain, and to compare the effect of IA LFJ PRF to IA corticosteroid injection (ICI). Pathology in the LFJ is a common source of lower back pain (LBP). It is responsible for chronic LBP in approximately 15% to 45% of patients. It has been reported that PRF stimulation can effectively reduce refractory joint pain.Methods:Sixty patients with LFJ pain were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
(29 reference statements)
0
32
0
3
Order By: Relevance
“…To the best of our knowledge, a total of four previous studies have reported the effects of IA LFJ corticosteroid injection in controlling LFJ-origin pain (30)(31)(32)(33). In 2011, Kawu et al (30) performed IA LFJ corticosteroid injection treatment in 10 patients, 90% of whom experienced a pain reduction of >50% according to visual analogue scale (VAS) scores 6 months after treatment.…”
Section: Group ------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, a total of four previous studies have reported the effects of IA LFJ corticosteroid injection in controlling LFJ-origin pain (30)(31)(32)(33). In 2011, Kawu et al (30) performed IA LFJ corticosteroid injection treatment in 10 patients, 90% of whom experienced a pain reduction of >50% according to visual analogue scale (VAS) scores 6 months after treatment.…”
Section: Group ------------------------------------------------------mentioning
confidence: 99%
“…In 2013, Ribeiro et al (32) performed IA LFJ corticosteroid injection treatment in 31 patients, who exhibited a ~50% reduction in mean VAS of pre-treatment scores 3 months after treatment. In 2017, Do et al (33) performed IA LFJ corticosteroid injection treatment in 30 patients and reported that the mean NRS score was reduced from 5 at pretreatment to 3.2 at 6 months following injection. In the current study, patients were classified into 3 groups according to lumbar axial MRI results.…”
Section: Group ------------------------------------------------------mentioning
confidence: 99%
“…Thus far, 10 previous studies have reported the effect of PRF stimulation on lumbosacral facet joint pain . Of these, 4 studies were randomized trials .…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, 10 previous studies have reported the effect of PRF stimulation on lumbosacral facet joint pain . Of these, 4 studies were randomized trials . In 2007, Tekin et al recruited 60 patients and performed PRF and CRF stimulations (temperature limitation: 80°C, 90 seconds, 22 gauge) on the lumbar medial branch, dividing the recruited patients into 3 equal‐sized groups (control, PRF, and CRF groups).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation